A Study on Big Data Hadoop Map Reduce Job Scheduling - Deshai, N; Venkataramana, S; Hemalatha, I; P. S. Varma, G (International Journal of Engineering and Technology, 2018)
A latest tera to zeta era has been created during huge volume of data sets, which keep on collected from different social networks, machine to machine devices, google, yahoo, sensors etc. called as big data. Because day by day double the data storage size, data processing power, data availability and digital world data size in zeta bytes. Apache Hadoop is latest market weapon to handle huge volume of data sets by its most popular components like hdfs and mapreduce, to achieve an efficient storage ability and efficient processing on massive volume of data sets. To design an effective algorithm is a key factor for selecting nodes are important, to optimize and acquire high performance in Big data. An efficient and useful survey, overview, advantages and disadvantages of these scheduling algorithms provided also identified throughout this paper.Â Â